1986
DOI: 10.1111/j.1348-0421.1986.tb02991.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Significance of Acinetobacter calcoaceticus: Analysis of Experimental Infection in Mice

Abstract: The phenomenon that mixed infection with certain species of bacteria and Acinetobacter calcoaceticus is more virulent than single infection was analyzed experimentally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 20 publications
(24 reference statements)
0
23
0
Order By: Relevance
“…In contrast, only a few reports describing different aspects related to the basic physiology, genetics, and molecular biology of this opportunistic pathogen (2,12,13,19,20,41,58) could be found during these literature searches. The apparent lack of suitable genetic methods such as random mutagenesis with transposable elements, which is a widely used approach to characterize bacteria genetically and functionally, appears to be the reason for the delay of the characterization of this human pathogen.…”
mentioning
confidence: 89%
“…In contrast, only a few reports describing different aspects related to the basic physiology, genetics, and molecular biology of this opportunistic pathogen (2,12,13,19,20,41,58) could be found during these literature searches. The apparent lack of suitable genetic methods such as random mutagenesis with transposable elements, which is a widely used approach to characterize bacteria genetically and functionally, appears to be the reason for the delay of the characterization of this human pathogen.…”
mentioning
confidence: 89%
“…Analysis of experimental infections in mice (49) showed that the slime ofA. baumannii is a virulence factor that acts by impairing the functions and cell structure of mice phagocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, most infections have occurred in patients compromised by either antibiotic therapy, respiratory instrumentation and manipulations, dialysis, or surgery (18,19,39,70). Thus, it was proposed that reduced host defenses and interaction with other bacterial species, rather than the expression of specific bacterial virulence factors (49), are the factors responsible for opportunistic infections caused by Acinetobacter species.…”
mentioning
confidence: 99%
“…), and there is experimental evidence suggesting that exopolysaccharide-producing strains of Acinetobacter spp. enhance the virulence of other gram-negative species in polymicrobial infections [52,53]. One could also speculate that chemical signals elaborated by the co-pathogen may activate biofilm formation by enhancing auto-inducer synthase production in A. baumannii, or vice versa [54].…”
mentioning
confidence: 99%